Ultrashort time to echo magnetic resonance techniques for the musculoskeletal system - Siriwanarangsun, Palanan; Statum, Sheronda; Biswas, Reni; Bae, Won C.; Chung, Christine B. (Quantitative Imaging in Medicine and Surgery, 2016)
Magnetic resonance (MR) imaging has been widely implemented as a non-invasive modality to investigate musculoskeletal (MSK) tissue disease, injury, and pathology. Advancements in MR sequences provide not only enhanced morphologic contrast for soft tissues, but also quantitative biochemical evaluation. Ultrashort time to echo (UTE) sequence, in particular, enables novel morphologic and quantitative evaluation of previously unseen MSK tissues. By using short minimum echo times (TE) below 1 msec, the UTE sequence can unveil short T2 properties of tissues including the deepest layers of the articular cartilage, cartilaginous endplate at the discovertebral junction, the meniscus, and the cortical bone. This article will discuss the application of UTE to evaluate these MSK tissues, starting with tissue structure, MR imaging appearance on standard versus short and ultrashort TE sequences, and provide the range of quantitative MR values found in literature.